"Øjet i Det Høje" - Fra elitetroppernes gudserfaring til menigmands gudsbillede - Jørgensen, Ninna (Religionsvidenskabeligt Tidsskrift, 1988)
What happens when a fixed set of conceptions are transferred from their original and natural “Sitz-im-Leben” to another social and cultural milieu? Something like this occurred when the literature which had developed in connection with the old monk movements was unleashed in the layman’s world, not the least due to the activities of the new beggar orders in the cities. This article closely studies one “exemplum” and its path from the earliest Middle Age times to the High Middle Ages with a new twist and on to become a part of the Dominican exemplum-corpus in the 15th century. The example demonstrates Gods leniency towards persons who have taken the vow of celibacy: in the face of menacing temptations, God miraculously reveals His eye, thereby either averting the planned sin or bringing on confession. Transferred into the daily lives and piety of ordinary people, the lenient guardian eye becomes a type of “super-ego”, which keeps an eye on the small sins of the individual, especially sexual escapades. In this manner the concept of God takes on the uncomfortable moralistic tones which have survived until this day.